THE IMPLEMENTATION OF GUESSING GAME IN TEACHING SPEAKING AT TENTH GRADE OF SENIOR HIGH SCHOOL - Nuraen Nuraen; Karyati Karyati (IKIP Siliwangi, 2018)
Guessing game becomes an interesting technique which can be implemented by English teachers to teach speaking. Beside rising so much fun, guessing games is believed could increase the students’ speaking skill. The aim of this paper is to describe the implementation of guessing game which is utilized by the teacher to improve students’ speaking ability at tenth grade of Senior High School. The researchers presented the instruction of how to use guessing games in teaching speaking by teacher in the classroom. Guessing games is a game to guess a thing, person or place, the one of student or group mention the clues and other students as a guesser guess that thing, person or place. Guessing game can help teacher to hire students’ participation and students’ courage in teaching English. The researchers did the observation to collect the data and find out classroom activity. The result of the research is that the teacher implemented the technique in several steps starting from making group, setting the students to discuss, making them present in front of the class by giving clues, and making the other groups guess what the speaker meant. By doing this activity, the students could develop their skill of speaking in fun way. Keywords : Speaking, Guessing Games.